Pemberian Video Edukasi Menurunkan Kecemasan Pasien Coronavirus Disease 2019 di Rumah Sakit - Emy Darma Yanti (Jurnal Ilmu Keperawatan Jiwa, 2021)
Patients who have been confirmed for Coronavirus Disease 2019 experience problems not only physically but also psychologically. This psychological impact can affect the patient's healing process if it is not addressed immediately. Especially for Coronavirus Disease 2019 patients who are treated in hospital isolation rooms. The purpose of this study was to analyze the effect of educational videos on the anxiety of Coronavirus Disease 2019 patients being treated at the Udayana University Hospital. This research is a quantitative study with the pre-experimental one group pretest-posttest design method which was conducted on 35 respondents with purposive sampling. Educational videos were given for five days with a video duration of five minutes. Data were collected using the Zung-Self Anxiety Rating Scale (ZSAS) instrument which consists of 20 statement items. The pre-test mean value was 24.51 and the post-test mean score was 22.14. The Wilcoxon test results obtained a p value of 0.000, which means that there is an effect of providing educational videos on the anxiety of Coronavirus Disease 2019 patients in the hospital. The provision of this educational video can reduce the anxiety felt by Coronavirus Disease 2019 patients while being treated in the Isolation Room at the Udayana University Hospital.